A Study on the Force/Position Hybrid Control Strategy for Eight-Axis Robotic Friction Stir Welding - Wenjun Yan; Yue Yu (Metals)
In aerospace and new-energy vehicle manufacturing, there is an increasing demand for the high-quality joining of large, curved aluminum alloy structures. This study presents a robotic friction stir welding (RFSW) system employing a force/position hybrid control. An eight-axis linkage platform integrates an electric spindle, multidimensional force sensors, and a laser displacement sensor, ensuring trajectory coordination between the robot and the positioner. By combining long-range constant displacement with small-range constant pressure—supplemented by an adaptive transition algorithm—the system regulates the axial stirring depth and downward force. The experimental results confirm that this approach effectively compensates for robotic flexibility, keeping weld depth and pressure deviations within 5%, significantly improving seam quality. Further welding verification was performed on typical curved panels for aerospace applications, and the results demonstrated strong adaptability under high-load, multi-DOF conditions, without crack formation. This research could advance the field toward more robust, automated, and adaptive RFSW solutions for aerospace, automotive, and other high-end manufacturing applications.